Doing away with cash? The welfare costs of abolishing cash - Gerhard Rösl; Franz Seitz; Karl-Heinz Tödter (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2017)
To broaden the scope of monetary policy, cash abolishment is often suggested as a means of breaking through the zero lower bound. However, practically nothing is said about the welfare costs of such a proposal. Rösl, Seitz and Tödter argue that the welfare costs of bypassing the zero lower bound can be analyzed analytically and empirically by assuming negative interest rates on cash holdings. They gauge the welfare effects of abolishing cash, both, for the euro area and for Germany. Their findings suggest that the welfare losses of negative interest rates incurred by money holders are large, notably if implemented in the current low interest rate environment. Imposing a negative interest rate of 3 percentage points on cash holdings and reducing the interest on all assets included in M3 creates a deadweight loss of exteuro 62bn for the euro area and of exteuro18bn for Germany. Therefore, the authors argue that cash abolishment or negative interest rates on cash to break through the zero lower bound at any price can hardly be a meaningful policy goal.
urn:nbn:de:hebis:30:3-431588
Keywords: E41; E21; E58; I3; 330; zero lower bound; cash abolishment; negative interest rates; welfare loss; compensated variation; deadweight loss